Effect of hydrophobic inclusions on polymer swelling kinetics studied by magnetic resonance imaging - Gajdošová, Michaela; Pěček, Daniel; Sarvašová, Nina; Grof, Zdeněk; Štěpánek, František (International journal of pharmaceutics, 2016)
The rate of drug release from polymer matrix-based sustained release formulations is often controlled by the thickness of a gel layer that forms upon contact with dissolution medium. The effect of formulation parameters on the kinetics of elementary rate processes that contribute to gel layer formation, such as water ingress, polymer swelling and erosion, is therefore of interest. In the present work, gel layer formation has been investigated by magnetic resonance imaging (MRI), which is a non-destructive method allowing direct visualization of effective water concentration inside the tablet and its surrounding. Using formulations with Levetiracetam as the active ingredient, HPMC as a hydrophilic matrix former and carnauba wax (CW) as a hydrophobic component in the matrix system, the effect of different ratios of these two ingredients on the kinetics of gel formation (MRI) and drug release (USP 4 like dissolution test) has been investigated and interpreted using a mathematical model.
Keywords: vosky; Magnetic Resonance Imaging; Hypromellose Derivatives; piracetam; magnetická rezonanční tomografie; MRI; Delayed-Action Preparations; HPMC; Hydrophobic and Hydrophilic Interactions; levetiracetam; rozpustnost; Waxes; Gel layer; deriváty hypromelózy; Piracetam; Tablets; Drug Liberation; uvolňování léčiv; Kinetics; tablety; Levetiracetam; teoretické modely; Solubility; léky s prodlouženým účinkem; Carnauba wax; Models, Theoretical; Drug dissolution; kinetika; hydrofobní a hydrofilní interakce